Pharmacodynamic safety of clopidogrel monotherapy in patients under oral anticoagulation with a vitamin K antagonist undergoing coronary stent implantation - Valina, Christian; Bömicke, Timo; Abdelrazek, Sherif; Eltaweel, Sara; Stratz, Christian; Ferenc, Miroslaw; Trenk, Dietmar; Chafai, Anja; Neumann, Franz Josef; Hochholzer, Willibald (Platelets, 2019)
Current guidelines recommend as treatment option in patients on oral anticoagulation (OAC) undergoing percutaneous coronary intervention (PCI) an antiplatelet monotherapy with clopidogrel if there is an increased risk for bleeding. However, retrospective data suggested a potential interaction of clopidogrel and the vitamin K antagonist (VKA) phenprocoumon leading to a diminished antiplatelet effect. This would increase the ischemic risk of patients treated with this combination. Thus, this prospective study sought to evaluate the pharmacodynamic effect of clopidogrel monotherapy in patients on phenprocoumon undergoing PCI and assessed clinical outcomes. This study enrolled 100 patients on aspirin plus clopidogrel (DAPT-cohort, without indication for VKA) and 100 patients on clopidogrel monotherapy plus phenprocoumon (OAC-cohort) undergoing elective PCI. Platelet reactivity was assessed by impedance aggregometry on day 1 following PCI. Ischemic (death, stroke, or myocardial infarction) and bleeding (BARC 2–5) events within 12 months were compared in a propensity score adjusted model. Platelet reactivity was not different in the OAC- and DAPT-cohort (187 [127–242] vs. 167 [126–218] AU×min; p = 0.23). Overall, 17 ischemic and 34 bleeding events were recorded during follow-up. The OAC-cohort showed a nonsignificant trend to an 80% higher incidence for ischemic and bleeding events in unadjusted analyses, which disappeared following adjustment (ischemic events HR 1.07, 95%-CI 0.32–3.59, p = 0.91; bleeding events HR 1.25, 95%-CI 0.46–3.40, p = 0.67). Following PCI, the pharmacodynamic effect of a clopidogrel monotherapy together with phenprocoumon is similar as compared to DAPT without a VKA, and not associated with an increased risk for ischemic events beyond the higher underlying baseline risk.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antiplatelet response; clopidogrel; coronary stent; oral anticoagulation